Test of a non-rectangular penalty area in the Euro 2016, Copa América 2016 and 2018 World Cup - Morales, C. A. (International Journal of Computer Science in Sport, 2019)
A recent proposal for a new geometry of the penalty area for football (soccer) has been put to the test by analyzing games of the 2016 continental championships, the European and South American ones, and the 2018 FIFA World Cup which are by far the three most important nations tournaments in the sport. All matches after the first stage were analyzed and some instances were found in these critical or knockout matches in which the game and its fairness would have improved if the penalty area had been drawn according to mathematics or a measure of actual scoring chance.